Evolution of Equity Information in the Balance Sheet - N. V. Tkachuk (Учёт. Анализ. Аудит)
The purpose of the study is to single out the main changes in the presentation of equity capital in the balance sheet made since the end of the 20th century to present day. Analysis, synthesis, deduction, etc. were chosen as the methodological basis, and scientific articles on this topic and regulatory documents formed the information base of the research. The article considers the main legal and economic prerequisites associated with changing the section on the organization’s own capital, as well as the history of the development of joint-stock companies during this period. The role of IFRS in the process of reforming the domestic accounting system in Russia is determined. The main changes in the presentation of existing items for equity are singled out. The change in the role of the “authorized capital” indicator is shown. The contradictions of the law “On Joint Stock Companies” regarding the formation and use of the reserve fund are identified. The stages of revaluation of fixed assets in Russia and its reflection in the accounting system are presented. The problem of regulation of share premium is analyzed, the content of articles removed from the section on the organization’s equity capital is described. We hope that the results of the study will be useful to researchers and specialists of the Ministry of Finance of the Russian Federation, and will also find practical reflection in new regulatory documents.